Comparative analysis of SPAD, NDVI, phenological and generative parameters of maize hybrids (Zea mays L.) - Ibtissem; Annabella; Adrienn (Növénytermelés, 2024)
Maize is a versatile multi-purpose crop that plays an essential role in the global food security. Meeting the needs of a growing population places the arable lands under the stress of intensive crop production. As the variations in climate conditions pose additional threats to maize production, the challenge focuses now on sustaining the crop yield, ensuring maximum yield and safeguarding crop protection. The experiment was carried out in 2023 at the Látókép Plant Production Experimental Site of the University of Debrecen (Hungary). The authors aimed to monitor the changes in spectral reflectance at leaf and canopy level at several growth stages of two different maize hybrids. Another objective was to evaluate their field agronomic performance and eventually compare between their results. Thus, SPAD, NDVI and LAI indices were recorded at five phenological stages (6-leaf, 12-leaf, silking, dough, maturity) of the development of two maize hybrids. Other agronomic characteristics of maize had been measured, including plant height, cob length, stalk diameter, grain moisture content, nitrogen accumulation and grain yield. The results demonstrated that Mv 352 hybrid had higher potential in terms of yield produced (13.64 t/ha) comparing to Fornad (12.93 t/ha), in addition to higher plant height, cob length and stalk diameter. The SPAD, NDVI and LAI recorded values showed higher values as the different growth stages developed and then decreased reaching the maturity phase. It was found that both hybrids had slight variation in their performance in this regard. However, in terms of nitrogen accumulation, Mv 352 had higher nitrogen content accumulated during the whole growing period in comparison with Fornad, highlighting its great performance in terms of nitrogen absorption and translocation. This study highlights the importance of monitoring SPAD, NDVI, and LAI values, as well as the plant nitrogen accumulation that provides insights into the physiological conditions of maize plants during the different growth stages, allowing for the early detection of stress factors, therefore enabling timely interventions. Additionally, this work emphasises the crucial aspect of performing these measurements for the selection and breeding of high-performing maize hybrids.